Response of Targeted Therapy Alongside Chemotherapy in an AML Patient with COVID-19 - Gaba, Radu (Medical Science: Recent Advances and Applications Vol. 1, 2025)
In this chapter, more detailed information was provided, which describes the first cycle treatment in a case of a newly diagnosed COVID-19 pneumonia in an AML patient. Pneumonia is a major cause of death among patients with leukemia. Venetoclax, a BH3-mimetic and selective BCL-2 inhibitor, is a medication used to treat adults with chronic lymphocytic leukemia (CLL), acute myeloid leukemia (AML), and small lymphocytic lymphoma (SLL). A 70-year-old normotensive, non-diabetic male was diagnosed with endocarditis with Aerococcus Viridans after a third molar extraction, followed by persistent fatigue, fever, weakness, nausea, and excessive sweating, especially at night. Afterwards, he was also diagnosed with AML M2/FAB (Acute myeloblastic leukemia with maturation M2). In this severe COVID-19 case, it was shown that the venetoclax treatment functioned, even in its first cycle, and moreover even without increasing the daily dose over 100 mg. One observed that the initial high value of monocytes (12620/µL) dropped after the 28-day period close to the normalization threshold (2500/µL), more exactly to 2360/µL. The positive response to venetoclax occurred even if the patient developed other comorbidities during that period, such as for example severe anemia within the disease, thrombocytopenia, and SIRS (systemic inflammatory response syndrome).